Structure determination of a sugar‐binding protein from the phytopathogenic bacterium Xanthomonas citri. Issue 5 (1st May 2014) - Medrano, Francisco Javier; de Souza, Cristiane Santos; Romero, Antonio; Balan, Andrea
<x xml:space="preserve">Abstract</x> The uptake of maltose and related sugars in Gram‐negative bacteria is mediated by an ABC transporter encompassing a periplasmic component (the maltose‐binding protein or MalE), a pore‐forming membrane protein (MalF and MalG) and a membrane‐associated ATPase (MalK). In the present study, the structure determination of the apo form of the putative maltose/trehalose‐binding protein (Xac‐MalE) from the citrus pathogen Xanthomonas citri in space group P6522 is described. The crystals contained two protein molecules in the asymmetric unit and diffracted to 2.8 Å resolution. Xac‐MalE conserves the structural and functional features of sugar‐binding proteins and a ligand‐binding pocket with similar characteristics to eight different orthologues, including the residues for maltose and trehalose interaction. This is the first structure of a sugar‐binding protein from a phytopathogenic bacterium, which is highly conserved in all species from the Xanthomonas genus.